Review on the Pavement-repairing Measures as a Condition for the Choice of Road-Maintenance Strategy - Ivana Nedevksa, Slobodan Ognjenovic, Andrej Pustovgar (MATEC Web of Conferences, 2017)
The road-maintenance strategies vary from one country to another, and even between the road management authorities within a one single country. It is not surprising, as there is not best maintenance method, nor a universal set of strategies that can be applied equally everywhere. Generally, there are strategies acceptable in certain conditions, but the factors influencing the selection process are diverse and very complex. This paper will present a review of the various measures that can be applied on the roads, which is certainly the basic condition of selection of an appropriate maintenance strategy.